Synergistic evolution of soil microaggregates biogeochemical processes driven by elevation gradients in Tongbai Mountain - Chunjie Li; Shili Guo; Songhao Shang (PLoS ONE, 2025)
The altitudinal gradient in mountainous areas triggers significant changes in landscape, climate, and vegetation, which in turn affect the vertical differentiation of soil type and their properties. Located in the transitional zone between the northern and southern climates of East Asia, Tongbai Mountain is of great geographical and ecological significance and is highly sensitive to global changes. However, systematic research on soil biogeochemical processes in the vertical zonation of mountainous areas in this transitional zone is still lacking. In this study, a sampling strategy based on altitude gradients was used, combined with a variety of advanced analytical techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), and Fourier transform infrared spectroscopy (FTIR), to comprehensively characterize the mineral composition, soil organic carbon (SOC), and heavy metal element distribution of soils at different altitudes in Mount Tongbai. The results showed that the mineral composition of the soil exhibited a clear gradient based on altitude. The Quartz content was higher at low and high altitudes, while the feldspar mineral content was highest in the middle altitudes. Illite increased with increasing altitude. SOC content increased significantly with increasing altitude, and hydroxyl, amino and aliphatic organic matter were enriched in high altitudes. Heavy metal elements such as Fe, Ti, Cu, and Zn increased in high altitudes, and the microstructure of soil aggregates in high altitudes was more complex and stable. Through a comprehensive analysis, MgO, Zr, 2929 cm⁻¹, 3423 cm⁻¹, and Cu were selected as sensitive biogeochemical factors in the vertical band spectrum. This study reveals for the first time the mechanism behind the coordinated evolution of soil minerals, SOC, and heavy metal elements driven by the altitude gradient. This deepens our understanding of biogeochemical processes in the vertical band spectrum of mountains in the climatic transition zone between North and South East Asia, and provides a scientific basis to formulate management strategies for mountain ecosystems in the climatic transition zone.